Highly dispersed CO adsorbent, preparation method thereof, and CO adsorption method
By dispersing Cu(I) and Ce on the porous carbon support, a high-dispersed CO adsorbent was prepared, which solved the problems of low CO adsorption capacity and insufficient removal depth of existing Cu(I)-loaded materials, and achieved efficient CO adsorption and removal effects.
Patent Information
- Application Number
- CN202111248933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-10-26
AI Technical Summary
Due to the low surface area and uneven Cu(I) dispersion of existing Cu(I) materials, the CO adsorption capacity is low and the CO removal depth is insufficient.
Using Ce as an auxiliary agent and a porous carbon carrier as a carrier, a highly dispersed CO adsorbent is prepared by providing a solution containing divalent copper salt and divalent cerium salt and calcining under an inert atmosphere.
The dispersion of the active component Cu(I) is improved, the CO adsorption capacity and CO removal depth are enhanced, and it can be effectively used for the depth removal of CO in pressure swing adsorption.
Smart Images

Figure CN116020409B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adsorption materials, and in particular to a highly dispersed CO adsorbent and a preparation method thereof, and a CO adsorption method. Background Art
[0002] CO is a colorless and odorless gas. The CO impurity in hydrogen is mainly due to the fact that the source of hydrogen is mostly coal-based hydrogen or petroleum reforming hydrogen. CO poisons fuel cells very quickly, mainly causing irreversible carbon corrosion and other permanent damage to the battery electrodes. At present, the hydrogen used in fuel cells has extremely high requirements for CO content. According to the national standard "GB / T 37244 Hydrogen for Proton Exchange Membrane Fuel Cell Vehicles", CO is less than or equal to 0.2ppm. Cu(I) adsorbents have attracted widespread attention due to their high adsorption capacity and high selectivity for CO, because the π complex bond formed between CO and Cu(I) ions on the adsorbent is stronger than the bond formed by van der Waals force. More importantly, in engineering operations such as normal temperature and reduced pressure, the π complex bond is still weak, and the adsorbed CO is easy to desorb, making it an ideal adsorbent in pressure swing adsorption applications.
[0003] CN110652960A discloses a CO adsorbent and a preparation method and application thereof. The CO adsorbent comprises a silicoaluminophosphate molecular sieve carrier and a monovalent copper compound. The preparation process of the adsorbent is simple.
[0004] The literature (Xue, C.; Hao, W.; Cheng, W.; Ma, J.; Li, R., Chemical Engineering Journal 2019, 375, 122049.) used copper (II) chloride and copper (II) carboxylate to impregnate activated carbon to prepare Cu(I) adsorbent, and then mildly heat treated it under vacuum conditions to obtain CuCl / AC adsorbent.
[0005] The literature (Yoon, T.-U.; Kim, MJ; Kim, A.-R.; Kang, JH; Ji, D.; Bae, Y.-S., Journal of Industrial and Engineering Chemistry 2020, 87, 102-109.) wet-impregnated Cu(II) into the mesopores of MIL-100(Fe), and used the reducing agent Na2SO3 to easily reduce Cu(II) to Cu(I) at room temperature.
[0006] However, these Cu(I)-loaded materials have low CO adsorption capacity and insufficient CO removal depth due to their low surface area, uneven Cu(I) dispersion, and easy aggregation of active components. Summary of the invention
[0007] The purpose of the present invention is to overcome the problem of insufficient removal depth of CO adsorbent in the prior art, and to provide a highly dispersed CO adsorbent and a preparation method thereof and a CO adsorption method. The active components in the adsorbent have high dispersion and deep CO removal depth, and can be used for CO removal in pressure swing adsorption.
[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a highly dispersed CO adsorbent, which comprises an auxiliary agent, a carrier and an active component loaded on the carrier, wherein the auxiliary agent is Ce, the carrier is a porous carbon carrier, and the active component is Cu(I).
[0009] A second aspect of the present invention provides a method for preparing a highly dispersed CO adsorbent, the method comprising:
[0010] (1) providing a solution containing a divalent copper salt and a divalent cerium salt;
[0011] (2) impregnating a porous carbon support with the solution and then calcining the carbon support under an inert atmosphere;
[0012] Wherein, the divalent copper salt is copper chloride.
[0013] A third aspect of the present invention provides a method for adsorbing CO, the method comprising:
[0014] contacting a gas containing CO with an adsorbent to adsorb the CO contained in the gas on the adsorbent;
[0015] Wherein, the adsorbent is the CO adsorbent described in the first aspect or the CO adsorbent prepared according to the method described in the second aspect.
[0016] Through the above technical scheme, the additive Ce contained in the highly dispersed CO adsorbent provided by the present invention can make the active component Cu(I) better dispersed on the surface of the porous carbon carrier, so that Cu(I) can be more effectively utilized. While having a high CO adsorption capacity, the CO removal depth of the adsorbent is also high, and can be used to deeply remove trace amounts of CO in hydrogen, so that it meets the requirements of hydrogen for fuel cell vehicles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 1 is the XRD diagram of the CO adsorbent prepared in Examples 1-3 and the comparative example;
[0018] Figure 2 1 is the CO adsorption breakthrough curve of the CO adsorbent prepared in Examples 1-3 and the comparative example. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] A first aspect of the present invention provides a highly dispersed CO adsorbent, which comprises an auxiliary agent, a carrier and an active component loaded on the carrier, wherein the auxiliary agent is Ce, the carrier is a porous carbon carrier, and the active component is Cu(I).
[0021] According to some embodiments of the present invention, the auxiliary agent is Ce, the carrier is a porous carbon carrier, and the active component is Cu(I). Wherein, Cu(I) refers to monovalent copper, such as CuCl. The Cu(I) adsorbent has a high adsorption capacity and selectivity for CO because there is a strong π complex bond between CO and Cu(I). The auxiliary agent Ce can make the active component Cu(I) better dispersed on the surface of the porous carbon carrier, so that Cu(I) can be used more effectively, so that the adsorbent has a high CO adsorption capacity and a high CO removal depth.
[0022] According to some embodiments of the present invention, the carrier is a porous carbon carrier, and the porous carbon carrier can be a porous carbon carrier conventionally used in the art for preparing a CO adsorbent. In order to further improve the CO adsorption capacity of the adsorbent, preferably, the porous carbon carrier is selected from at least one of activated carbon, graphene, carbon and carbon black, and more preferably activated carbon. The activated carbon can be shaped activated carbon or powdered activated carbon.
[0023] According to some embodiments of the present invention, preferably, the BET specific surface area of the porous carbon carrier is 800-1800 m 2 / g, preferably 1000-1500m 2 The use of the porous carbon carrier having a specific BET specific surface area is beneficial to the uniform dispersion and loading of the active components.
[0024] According to some embodiments of the present invention, the pore structure properties of the porous carbon support are detected by the BET test method, specifically using a Quantachrome AS-6B analyzer, and the specific surface area of the porous carbon support is obtained by the Brunauer-Emmett-Taller (BET) method.
[0025] According to some embodiments of the present invention, preferably, in the CO adsorbent, the loading amount of Cu(I) on the porous carbon carrier is 4-8 mmol / g, preferably 5-7 mmol / g.
[0026] According to some embodiments of the present invention, preferably, in the CO adsorbent, the loading amount of Ce on the porous carbon carrier is 0.1-1.5 mmol / g, preferably 0.2-1 mmol / g.
[0027] According to some embodiments of the present invention, preferably, in the CO adsorbent, the molar ratio of Cu(I) to Ce is 6-60: 1, preferably 6-30: 1. The molar ratio of Cu(I) to Ce is limited to the above range, which is conducive to high dispersion of active components.
[0028] According to some embodiments of the present invention, in the CO adsorbent, each component is determined by calculating the feed amount of each raw material.
[0029] According to some embodiments of the present invention, preferably, after XRD detection, the CO adsorbent has no peak in the range of 2θ angle of 20° to 30° and / or in the range of 2θ angle of 40° to 50°. That is, no obvious diffraction peak of CuCl (2θ=28.5° and 47.4°, corresponding to the characteristic diffraction peak of CuCl) is observed in the XRD spectrum of the CO adsorbent, indicating that the active component Cu(I) in the CO adsorbent is highly dispersed on the surface of the carrier.
[0030] According to some embodiments of the present invention, the composition of the CO adsorbent, the structure or morphology of the internal atoms or molecules, and other information are obtained by XRD. The model of the XRD diffractometer used is Bruker D8 ADVANCE, using a Cu target, Kα radiation, a tube voltage (40 kV) and a scanning range of 10°-60°.
[0031] A second aspect of the present invention provides a method for preparing a highly dispersed CO adsorbent, the method comprising:
[0032] (1) providing a solution containing a divalent copper salt and a divalent cerium salt;
[0033] (2) impregnating a porous carbon support with the solution and then calcining the carbon support under an inert atmosphere;
[0034] Wherein, the divalent copper salt is copper chloride.
[0035] According to some embodiments of the present invention, in step (1), the divalent copper salt is copper chloride, which may be copper chloride containing water of crystallization or copper chloride without water of crystallization. Preferably, the copper salt is copper chloride dihydrate.
[0036] According to some embodiments of the present invention, in step (1), the divalent cerium salt can be selected from a wide range and can be a water-soluble divalent cerium salt conventionally used in the art, preferably at least one of cerium acetate, cerium chloride and cerium nitrate, more preferably cerium acetate. The divalent cerium salt can be a divalent cerium salt containing crystal water or a divalent cerium salt not containing crystal water.
[0037] According to some embodiments of the present invention, in step (1), the molar ratio of the divalent copper salt to the divalent cerium salt is 6-60:1, preferably 6-30:1, calculated as metal elements.
[0038] According to some embodiments of the present invention, the porous carbon carrier can be selected with reference to the above, which will not be described in detail here.
[0039] According to some embodiments of the present invention, in step (1), the present invention has no particular limitation on the method for forming the solution, as long as a uniform solution can be formed. Preferably, the divalent copper salt and the divalent cerium salt are dissolved in a solvent to form the solution, and more preferably, the solvent is water.
[0040] According to some embodiments of the present invention, in step (2), the porous carbon support is impregnated with the solution. The present invention has no particular limitation on the impregnation method, and any impregnation method known in the art can be used, as long as copper and cerium can be loaded on the porous carbon support. In order to better load copper and cerium on the porous carbon support and improve the loading uniformity of the active component Cu (I), preferably, an equal volume impregnation method is used, and more preferably, the ratio of the solution to the porous carbon support is 5-12mL:5g, preferably 8-10mL:5g.
[0041] According to some embodiments of the present invention, preferably, after the porous carbon carrier is impregnated with the solution and before calcination, a drying step is also included. The drying method and conditions can refer to the prior art. For example, the drying temperature can be 60-80°C and the drying time can be 12-24h.
[0042] According to some embodiments of the present invention, preferably, in step (2), the calcination conditions include: a calcination temperature of 200-500°C, preferably 300-360°C; a calcination time of 2-8h, preferably 3-4h; a heating rate of 2-10°C / min, preferably 4-5°C / min.
[0043] According to some embodiments of the present invention, preferably, the inert atmosphere is provided by at least one inert gas selected from nitrogen, helium and argon; more preferably, the flow rate of the inert gas is 40-120 mL / min, preferably 50-80 mL / min.
[0044] According to some embodiments of the present invention, preferably, the divalent copper salt, the divalent cerium salt and the porous carbon carrier are used in such an amount that in the prepared CO adsorbent, the loading amount of Cu(I) on the porous carbon carrier is 4-8 mmol / g, preferably 5-7 mmol / g.
[0045] According to some embodiments of the present invention, preferably, the divalent copper salt, the divalent cerium salt and the porous carbon carrier are used in such an amount that, in the prepared CO adsorbent, the loading amount of Ce on the porous carbon carrier is 0.1-1.5 mmol / g, preferably 0.2-1 mmol / g.
[0046] According to a particularly preferred embodiment of the present invention, the method for preparing a dual-active component CO adsorbent comprises:
[0047] (S1) providing a solution containing a divalent copper salt and a divalent cerium salt;
[0048] (S2) impregnating a porous carbon support with the solution, and then calcining the porous carbon support under an inert atmosphere;
[0049] The divalent copper salt is copper chloride dihydrate, the divalent cerium salt is cerium acetate, and the BET specific surface area of the porous carbon carrier is 800-1800m 2 / g; in terms of metal elements, the molar ratio of the divalent copper salt to the divalent cerium salt is 6-60:1; the ratio of the solution to the porous carbon carrier is 5-12mL:5g; the calcination conditions include: a calcination temperature of 200-500°C and a calcination time of 2-8h.
[0050] According to some embodiments of the present invention, the method is simple to operate, and the active component Cu(I) has good dispersion on the surface of the porous carbon support.
[0051] A third aspect of the present invention provides a method for adsorbing CO, the method comprising:
[0052] contacting a gas containing CO with an adsorbent to adsorb the CO contained in the gas on the adsorbent;
[0053] Wherein, the adsorbent is the CO adsorbent described in the first aspect or the CO adsorbent prepared according to the method described in the second aspect.
[0054] According to some embodiments of the present invention, preferably, the contacting conditions include: a temperature of 25-40°C and a pressure of 1 Bar-21 Bar; more preferably, the contacting is performed at room temperature (25°C) and normal pressure (100 kPa (1 Bar)). During the contacting process, the CO adsorbent adsorbs CO, causing a pressure drop, and gradually reaches adsorption equilibrium, thereby obtaining an adsorbent adsorbing carbon dioxide.
[0055] According to some embodiments of the present invention, in order to improve the adsorption effect of the CO adsorbent on CO, preferably, the adsorption method further comprises activating the adsorbent under an inert gas environment or a reducing gas environment before the contacting, wherein the activation can remove impurities such as water and air adsorbed in the adsorbent. Preferably, the activation conditions include: a temperature of 200-350°C and a time of 1-2 hours.
[0056] According to some embodiments of the present invention, preferably, the gas containing CO is a mixed gas of hydrogen and CO, and more preferably, the concentration of CO in the mixed gas is 1-50 ppm. Further preferably, the mixed gas is a gas used as a fuel cell fuel. The CO adsorbent provided by the present invention is particularly suitable for removing CO from hydrogen used as a fuel cell fuel, and is particularly suitable for deeply removing trace amounts of CO from hydrogen to meet the requirements of hydrogen for fuel cell vehicles.
[0057] According to some embodiments of the present invention, preferably, the adsorption method further comprises heating and / or reducing the pressure of the adsorbent adsorbed with carbon dioxide, wherein the heating and / or reducing the pressure can desorb the CO adsorbed on the CO adsorbent, thereby recovering the CO adsorbent and recycling it for the adsorption of CO.
[0058] According to some embodiments of the present invention, preferably, the heating conditions include: a temperature of 40-100° C. and a time of 1-3 hours.
[0059] According to some embodiments of the present invention, preferably, the decompression conditions include: a pressure of 50-100 kPa and a time of 1-3 hours.
[0060] According to some embodiments of the present invention, for hydrogen with a CO concentration of 5 ppm, under the conditions of an adsorption temperature of 40° C. and an adsorption pressure of 2.1 MPa, the CO removal depth of the CO adsorbent provided by the present invention can reach below 0.09 ppm.
[0061] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:
[0062] Unless otherwise specified, all reagents used in the present invention are analytically pure and commercially available.
[0063] The activated carbon was purchased from Beijing Inokai Technology Co., Ltd. (supplier), the model / brand is Norit ROW, and the BET specific surface area is: 1400m 2 / g.
[0064] The specific surface area of the porous carbon support was tested by the BET test method, which was determined by a Quantachrome AS-6B analyzer, and the specific surface area of the porous carbon support was obtained by the Brunauer-Emmett-Taller (BET) method.
[0065] The model of the XRD diffractometer used was Bruker D8 ADVANCE, using a Cu target, Kα radiation, a tube voltage (40 kV) and a scanning range of 10°-60°.
[0066] In the following examples and comparative examples, the loading amount of the active component and / or auxiliary agent of the CO adsorbent is determined by calculation based on the feed amount of each raw material.
[0067] Examples 1-3 are used to illustrate CO adsorbents and their preparation methods
[0068] Example 1
[0069] 1) Dissolve 5.11 g of cupric chloride dihydrate in 7 mL of deionized water, add 1.59 g of cerium acetate and stir to dissolve to obtain a solution, wherein the molar ratio of cupric chloride dihydrate to cerium acetate is 6:1 based on the metal element.
[0070] 2) Add 5 g of activated carbon and immerse an equal volume in the solution, and let it stand for 0.5 h.
[0071] 3) The product obtained in step 2) was placed in an oven at 60° C. and dried overnight to obtain material 1.
[0072] 4) placing material 1 in a tubular furnace under nitrogen protection and calcining it, wherein the nitrogen flow rate is 50 mL / min, the heating rate is 4°C / min, the calcination temperature is 360°C, and the calcination time is 4 h to obtain a CO adsorbent, wherein the loading amount of Cu(I) on activated carbon is 6 mmol / g, and the loading amount of Ce on activated carbon is 1 mmol / g.
[0073] Example 2
[0074] 1) Dissolve 5.11 g of cupric chloride dihydrate in 7 mL of deionized water, add 0.79 g of cerium acetate and stir to dissolve to obtain a solution, wherein the molar ratio of cupric chloride dihydrate to cerium acetate is 6:0.5 based on metal elements.
[0075] 2) Add 5 g of activated carbon and immerse an equal volume in the solution, and let it stand for 0.5 h.
[0076] 3) The product obtained in step 2) was placed in an oven at 60° C. and dried overnight to obtain material 1.
[0077] 4) placing material 1 in a tubular furnace under nitrogen protection and calcining it, wherein the nitrogen flow rate is 50 mL / min, the heating rate is 4°C / min, the calcination temperature is 360°C, and the calcination time is 4 h to obtain a CO adsorbent, wherein the loading amount of Cu(I) on activated carbon is 6 mmol / g, and the loading amount of Ce on activated carbon is 0.5 mmol / g.
[0078] Example 3
[0079] 1) Dissolve 5.11 g of cupric chloride dihydrate in 7 mL of deionized water, add 0.32 g of cerium acetate and stir to dissolve to obtain a solution, wherein the molar ratio of cupric chloride dihydrate to cerium acetate is 3:0.1 based on metal elements.
[0080] 2) Add 5 g of activated carbon and immerse an equal volume in the solution, and let it stand for 0.5 h.
[0081] 3) The product obtained in step 2) was placed in an oven at 60° C. and dried overnight to obtain material 1.
[0082] 4) placing material 1 in a tubular furnace under nitrogen protection and calcining it, wherein the nitrogen flow rate is 50 mL / min, the heating rate is 4°C / min, the calcination temperature is 360°C, and the calcination time is 4 h to obtain a CO adsorbent, wherein the loading amount of Cu(I) on activated carbon is 6 mmol / g, and the loading amount of Ce on activated carbon is 0.2 mmol / g.
[0083] Comparative Example
[0084] 1) Dissolve 10.23 g of cupric chloride dihydrate in 14 mL of deionized water to obtain a solution.
[0085] 2) Add 10g of activated carbon and immerse an equal volume in the solution, and let it stand for 0.5h.
[0086] 3) The product obtained in step 2) was placed in an oven at 60° C. and dried overnight to obtain material 1.
[0087] 4) placing material 1 in a tubular furnace under nitrogen protection and calcining it, wherein the nitrogen flow rate is 50 mL / min, the heating rate is 4°C / min, the calcination temperature is 360°C, and the calcination time is 4 h to obtain a CO adsorbent, wherein the loading amount of Cu(I) on activated carbon is 6 mmol / g.
[0088] Characterization of materials:
[0089] Figure 1 is the XRD diagram of the CO adsorbent prepared in Examples 1-3 and Comparative Example, Figure 1It can be seen that the XRD spectrum of the CO adsorbent of the comparative example shows the diffraction peak of CuCl, while the intensity of the CuCl diffraction peak in the XRD spectrum of the CO adsorbents of Examples 1 and 2 is weakened, and the diffraction peak of CuCl is almost not observed in the XRD spectrum of the CO adsorbent of Example 3, indicating that CuCl is highly dispersed on the surface of the activated carbon.
[0090] Test Case
[0091] Test method for dynamic adsorption capacity of CO: The CO adsorbents prepared in Examples 1-3 and the comparative example were respectively loaded into a stainless steel fixed bed reactor and activated at 300°C for 2h under a nitrogen atmosphere. Hydrogen with a CO concentration of 5ppm was introduced, the adsorption temperature was 40°C, the adsorption pressure was 2.1MPa, and the volume space velocity was 3000h-1. -1 The concentration of CO in the product hydrogen is detected by gas chromatography. When the concentration of CO in the product gas exceeds 0.2 ppm, the adsorbent is judged to have penetrated.
[0092] Figure 2 is the CO adsorption breakthrough curve of the CO adsorbent prepared in Examples 1-3 and the comparative example, Figure 2 It can be seen that the CO penetration time of the CO adsorbents of Examples 1-3 and the comparative example is about 180 minutes. Figure 2 As shown in Table 1, the CO removal depth of the adsorbent of Example 1 is 0.09 ppm, the CO removal depth of the adsorbent of Example 2 is 0.07 ppm, the CO removal depth of the adsorbent of Example 3 is 0.06 ppm, and the CO removal depth of the adsorbent of the comparative example is 0.11 ppm. The CO removal depths of the adsorbents of Examples 1-3 are all better than those of the comparative example, indicating that the auxiliary agent Ce contained in the CO adsorbent of the present invention is beneficial to the dispersion of the active component Cu(I) in the porous carbon carrier, thereby improving the CO removal depth of the adsorbent.
[0093] Table 1
[0094] Adsorbent CO removal depth (ppm) Example 1 0.09 Example 2 0.07 Example 3 0.06 Comparative Example 0.11
[0095] It can be seen from the above results that, compared with the CO adsorbent with a single active component, the additive Ce contained in the highly dispersed CO adsorbent provided by the present invention can make the active component Cu(I) better dispersed on the surface of the porous carbon carrier, so that Cu(I) can be more effectively utilized. While having a higher CO adsorption capacity, the CO removal depth of the adsorbent is also high.
[0096] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A highly dispersed CO adsorbent, characterized in that: The CO adsorbent comprises an auxiliary agent, a carrier and an active component loaded on the carrier, wherein the auxiliary agent is Ce, the carrier is a porous carbon carrier, and the active component is Cu(I); In the CO adsorbent, the loading amount of Cu(I) on the porous carbon carrier is 4-7 mmol / g, and the loading amount of Ce on the porous carbon carrier is 0.1-1.5 mmol / g; The CO adsorbent is prepared by the following preparation method, comprising: (1) providing a solution containing a divalent copper salt and cerium acetate; wherein the divalent copper salt is copper chloride; (2) The porous carbon support is impregnated with the solution and then calcined under an inert atmosphere.
2. The CO adsorbent according to claim 1, wherein The porous carbon carrier is selected from at least one of activated carbon, graphene, carbon and carbon black.
3. The CO adsorbent according to claim 1 or 2, wherein: The porous carbon carrier is activated carbon.
4. The CO adsorbent according to claim 1 or 2, wherein: The BET specific surface area of the porous carbon carrier is 800-1800 m 2 / g.
5. The CO adsorbent according to claim 4, wherein: The BET specific surface area of the porous carbon carrier is 1000-1500m 2 / g.
6. The CO adsorbent according to claim 1 or 2, wherein: According to XRD detection, the CO adsorbent has no sharp peak within the range of 20° to 30° at a 2θ angle and / or within the range of 40° to 50° at a 2θ angle.
7. The CO adsorbent according to claim 1 or 2, wherein: In the CO adsorbent, the loading amount of Cu(I) on the porous carbon carrier is 5-7 mmol / g.
8. The CO adsorbent according to claim 1 or 2, wherein: In the CO adsorbent, the loading amount of Ce on the porous carbon carrier is 0.2-1 mmol / g.
9. The CO adsorbent according to claim 1 or 2, wherein: In the CO adsorbent, the molar ratio of Cu(I) to Ce is 6-60:
1.
10. The CO adsorbent according to claim 9, wherein In the CO adsorbent, the molar ratio of Cu(I) to Ce is 6-30:
1.
11. The CO adsorbent according to claim 1 or 2, wherein: In step (2), the ratio of the solution to the porous carbon support is 5-12 mL: 5 g.
12. The CO adsorbent according to claim 11, wherein In step (2), the ratio of the solution to the porous carbon support is 8-10 mL: 5 g.
13. The CO adsorbent according to claim 1 or 2, wherein: In step (2), the calcination conditions include: calcination temperature of 200-500°C; calcination time of 2-8h; and heating rate of 2-10°C / min.
14. The CO adsorbent according to claim 13, wherein In step (2), the calcination conditions include: calcination temperature of 300-360°C; calcination time of 3-4h; and heating rate of 4-5°C / min.
15. The CO adsorbent according to claim 1 or 2, wherein: The inert atmosphere is provided by at least one inert gas selected from the group consisting of nitrogen, helium and argon.
16. The CO adsorbent according to claim 15, wherein The flow rate of the inert gas is 40-120 mL / min.
17. The CO adsorbent according to claim 16, wherein: The flow rate of the inert gas is 50-80 mL / min.
18. A method for adsorbing CO, comprising: contacting a gas containing CO with an adsorbent to adsorb the CO contained in the gas on the adsorbent; Wherein, the adsorbent is the CO adsorbent described in any one of claims 1-17.
19. The method according to claim 18, wherein: The adsorption method further comprises activating the adsorbent under an inert gas environment or a reducing gas environment before the contacting.
Citation Information
Patent Citations
High-strength gas purifying and separating adsorbent as well as preparation and application thereof
CN101927152A
Adsorbent for deeply removing carbon monoxide in hydrogen, preparation method of adsorbent and method for removing carbon monoxide in hydrogen by adopting adsorbent
CN113351159A